ORGANIZATIONAL CITIZENSHIP BEHAVIOR AND JOB PERFORMANCE OF FLIGHT ATTENDANT: ROLE OF WORK-LIFE BALANCE - Somsila, Krittiya; Onlamai , Wanida; Pollasan, Tharit (Journal of Liberal Arts and Management Science Kasetsart University, 2025)
The flight attendant profession is characterized by high-pressure service demands and time constraints, which impact both health and job performance. This study, therefore, aims to investigate the factors of work-life balance (WLB) that influence organizational citizenship behavior (OCB) and job performance among flight attendants in Thailand. Employing the Job Demands-Resources (JD-R) Model, the study analyzes the various dimensions of WLB. Data were collected from 354 flight attendants in Thailand and analyzed using Structural Equation Modeling (PLS-SEM). The findings indicate that the dimensions of work, family, financial, and intellectual balance directly and positively influence OCB, reflecting the model’s motivational pathway where resources such as supervisor support and self-confidence foster work engagement. Conversely, the dimensions of time and family balance directly impact job performance, supporting the health impairment pathway, which suggests that excessive job demands or role conflict can lead to burnout and negatively affect performance. Furthermore, OCB was identified as a significant mechanism for translating personal resources into organizational performance. These findings offer actionable insights for airline management to formulate policies aimed at reducing job demands while increasing job and personal resources, thereby fostering sustainable well-being and job performance.